O-plane backreaction and scale separation in type IIA flux vacua - Junghans, Daniel (Fortschritte der Physik, 2020)
The author constructs AdS4 flux vacua of type IIA string theory in the supergravity (large volume, small gs) regime, including the backreaction of O6-planes. The solutions are the localized versions ...
First published: 28 April 2020
Gesehen am 15.11.2021